The Associations Between Media Use, Midpoint of Sleep, and Sleep Quality in German Preschoolers: A Mediation Analysis Based on the Ulm SPATZ Health Study - Ricci, Cristian (Nat Sci Sleep, 2021)
INTRODUCTION: The relation of electronic media use with sleep quality among preschoolers is a matter of ongoing debate. Longitudinal data are scarce and do not account for sleeping schedules. METHODS: We used the German Children’s Sleep Habits Questionnaire to measure parent-reported child’s sleep quality; its score is computed by the sum of 34 items defined by a 1–3 level Likert scale (score ranging 34–102), with higher values representing lower sleep quality. A causal mediation analysis of these relations using data from the Ulm SPATZ Health Study in Germany was conducted. Repeated data on electronic media use, book reading, sleep quality, sleep duration, and midpoint of sleep were prospectively collected yearly from ages 4 to 6 years (n=563) during parent’s working days and free days. RESULTS: We observed negative correlations of sleep quality with sleep duration and midpoint of sleep at ages 4–5 (R=−0.21 to −0.10), which attenuated with age 6 years. Sleep duration and midpoint of sleep were strongly positively correlated at all ages (R=0.55–0.95). We observed significant negative associations between total electronic media use and TV/DVD watching, while book reading did neither affect the sleep quality score nor sleep duration or midpoint of sleep. We found little evidence for an indirect negative effect of media use on sleep quality via sleep duration or midpoint of sleep, indicating that media use acts independently on sleep duration, midpoint of sleep, and sleep quality. Non-statistically significant associations of sleep duration and midpoint of sleep on sleep quality indicate that these are independent aspects of sleep adequacy. Evidence for this was stronger during free days. CONCLUSION: Media use acted on sleep quality through a direct effect in a prospective fashion. Thus, we conclude that electronic media use increases the risk for sleep impairments in German preschoolers, while book reading seems to be a safe and healthy alternative.